Personal finance - Garman, E. Thomas; Forgue, Raymond E. (Cengage Learning, 2015)
Using a structured, step-by-step approach, this market-leading text helps students learn how to save and invest, manage student loans, file taxes, decrease credit card debt, and plan for the future. Building on the success of previous editions, the new Twelfth Edition continues to engage students and focus their attention on critical concepts they need to succeed in class and to manage their finances wisely for a lifetime.